1985
DOI: 10.1159/000206197
|View full text |Cite
|
Sign up to set email alerts
|

Cryoglobulinemia and Fibronectin

Abstract: Isolated and washed cryoglobulins obtained from 30 patients with different diseases were studied for the presence of fibronectin by immunoelectrophoresis. Two of the isolated cryoglobulins were of the type I, 3 were of the type II, while the other 25 were of type III. Despite extensive washing, fibronectin was detected in all the cryoprecipitates. Our results indicate the constant presence of fibronectin in the cryoprecipitates from patients with different diseases and types of cryglobulin. The possible mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…In this regard, the constant presence of fibronectin in the cryoprecipitates from patients with cryoglobulinemia is intriguing. [40][41][42] Although its significance remains to be determined, an attractive hypothesis would be that fibronectin present in cryoglobulins may promote glomerular localization through interaction with its receptor, such as a5b1 integrin, on endothelial cells 43 and/or the extracellular matrix of the glomerular basement membrane and the mesangium. Whether the extent of terminal sialylation contributes to the interaction of cryogenic IgG3 with fibronectin is an additional issue that needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the constant presence of fibronectin in the cryoprecipitates from patients with cryoglobulinemia is intriguing. [40][41][42] Although its significance remains to be determined, an attractive hypothesis would be that fibronectin present in cryoglobulins may promote glomerular localization through interaction with its receptor, such as a5b1 integrin, on endothelial cells 43 and/or the extracellular matrix of the glomerular basement membrane and the mesangium. Whether the extent of terminal sialylation contributes to the interaction of cryogenic IgG3 with fibronectin is an additional issue that needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The major feature of this rheumatic disorder is the presence in the circulation of cold-precipitable immune complex es (cryoglobulins) [2], These are produced as the con sequence of the interaction between rheumatoid fac tor synthesized by an expanded clone of B lympho cytes [3] and polyclonal IgG. Cryoglobulins, once formed, are responsible for widespread endothelial damage with the clinical features of multiorgan vas culitis [4], that can be partially treated by mechanical removal of these immune complexes [5], It has recent ly been shown that fibronectin (FN), a high molecular weight multifunctional plasma glycoprotein [6,7], mainly synthesized by endothelial cells and constantly present in fibrin clots [8], coprecipitates with cryoglo bulins [9,10], Moreover we recently demonstrated that circulating cross-linked fibrin degradation prod ucts are abnormally increased in EMC patients with higher values observed in those with more severe dis ease [11]. These findings suggest that chronic dissemi nated intravascular coagulation is a feature of EMC and that activation of the coagulation cascade may be involved in the pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Annexin II can bind DNA-containing IC on MCs (Aarli et al, 1991; Yung et al, 2010) and monomeric IgG on placental cells (Kristoffersen et al, 1994), CD7 can bind IgM on lung EnCs (Nishimura et al, 2006), fibronectin can complex with cryoglobulins to bind integrins on MCs (Fujii et al, 2003; Villar et al, 1985), and the TfR can bind to IgA and IgA IC on MCs (Moura et al, 2001). However, when tested fibronectin did not mediate HA-IgG binding (Fujii et al, 2003).…”
Section: Discussionmentioning
confidence: 99%